"I want to save my life": Conceptions of cervical and breast cancer screening among urban immigrant women of South Asian and Chinese origin. (December 2016) - Hulme, Jennifer; Moravac, Catherine; Ahmad, Farah; Cleverly, Shelley; Lofters, Aisha; Ginsburg, Ophira; Dunn, Sheila
Abstract Background Breast and cervical cancer screening rates remain low among immigrant women and those of low socioeconomic status. The Cancer Awareness: Ready for Education and Screening (CARES) project ran a peer-led multi-lingual educational program between 2012 and 2014 to reach under and never-screened women in Central Toronto, where breast and cervical cancer screening rates remain low. The objective of this qualitative study was to better understand how Chinese and South Asian immigrants – the largest and most under-screened immigrant groups according to national and provincial statistics - conceive of breast and cervical cancer screening. We explored their experiences with screening to date. We explicitly inquired about their perceptions of the health care system, their screening experiences with family physicians and strategies that would support screening in their communities. Methods We conducted 22 individual interviews and two focus groups in Bengali and Mandarin with participants who had attended CARES educational sessions. Transcripts were coded through an iterative constant comparative and interpretative approach. Results Themes fell into five major, overlapping domains: risk perception and concepts of preventative health and screening; health system engagement and the embedded experience with screening; fear of cancer and procedural pain; self-efficacy, obligation, and willingness to be screened; newcomer barriers and competing priorities. These domains all overlap, and contribute to screening behaviours. Immigrant women experienced a number of barriers to screening related to 'navigating newness', including transportation, language barriers, arrangements for time off work and childcare. Fear of screening and fear of cancer took many forms; painful or traumatic encounters with screening were described. Female gender of the provider was paramount for both groups. Newly screened South Asian women were reassured by their first encounter with screening. Some Chinese women preferred the anonymous screening options available in China. Women generally endorsed a willingness to be screened, and even offered to organize women in their community hubs to access screening. Conclusions The experience of South Asian and Chinese immigrant women suggests that under and never-screened newcomers may be effectively integrated into screening programs through existing primary care networks, cultural-group specific outreach, and expanding access to convenient community -based screening.